Transition metal dichalcogenides: magneto-polarons and resonant Raman scattering - Trallero-Giner, C.; Santiago-Pérez, D. G.; Tkachenko, D. V.; Marques, G. E.; Fomin, V. M. (Frontiers in Physics, 2024)
Topological two-dimensional transition metal dichalcogenides (TMDs) have a wide range of promising applications and are the subject of intense basic scientific research. Due to the existence of a direct optical band gap, nano-optics and nano-optoelectronics employing monolayer TMDs are at the centre of the development of next-generation devices. Magneto-resonant Raman scattering (MRRS) is a non-destructive fundamental technique that enables the study of magnetoelectronic levels for TMD semiconductor device applications and hitherto unexplored optical transitions. Raman intensity in Faraday backscattering configuration as a function of the magnetic field B, the laser energy and the circular polarization of light, reveals set of incoming and outgoing resonances with particular spin orientations and magneto-optical interband transitions at the K-and K -valleys of the Brillouin zone. This fact unequivocally allows for a straightforward determination of the important band parameters of the TMD materials. A generalization of the MRRS theory is performed for the description of the magneto-polaron (MP) effects in the firstorder light scattering process. It shows how strongly the simultaneous presence of the conduction and valence bands modifies the MP energy spectrum. The resonant MP Raman intensity reveals three resonant splittings of double avoided-crossing levels reflecting the electron-hole pair energy spectrum. The scattering profile allows for quantifying the relative contribution of the conduction 1 C. Trallero-Giner et al. TMDs: Magneto-Polarons and Raman Scattering and valence bands in the formation of MPs. Many avoided crossing points due to the electronphonon interaction in the MP spectrum, a superposition of the electron and hole states in the excitation branches, and their impact on Raman scattering are exceptional features of ML TMDs. On these grounds, the reported theoretical studies open a pathway towards MRRS and resonant MP Raman scattering characterization of two-dimensional materials.